Phenology, growth, productivity, and profitability of mungbean as affected by potassium and organic matter under water stress vs. no water stress conditions. (7th January 2022) - Amanullah,; Yar, Mohammad; Khalid, Shah; Elshikh, Mohamed Soliman; Akram, Hafiz M.; Imran,; Al-Tawaha, Abdel Rahman M.; Ahmad, Manzoor; Muhammad, Asim; Ullah, Saif; Ali, Izhar; Fahad, Shah; et al.
Abstract: Pulses low yield in the arid and semiarid climates are imbalanced use of chemical fertilizers and no use of organic matter (animal and crop residues incorporation). The hypothesis was tested that integrated use of potassium (K) and animal manures could increase mungbean ( Vigna radiata L. Wilczek) productivity and profitability in the semiarid climate of Peshawar. A field experiment was carried out to investigate the effect of organic matter (composted animal manures) (5, 10, and 15 t ha −1 ) and potassium (30, 45, and 60 kg ha −1 ) under irrigated (three irrigations, no water stress) and dryland or limited irrigated (one irrigation, water stresses before flowering and after pod formation) condition on mungbean (cv. Ramazan 92). The experiment was carried out in the summer of 2017 at Agronomy Research Farm, the results revealed that crop under no water stress had delayed phenological development (took more days to flowering, pod formation, and physiological maturity), better growth by producing taller plants with a more number of leaves, nodules, and pods plant −1, seeds pod −1, heavy 1000-grains weight, higher biological and grain yields than water stress condition. The experiment also confirmed that the combination of the highest rate of K and organic matter had improved the vegetative growth and development, and significantly increased yield and yield contributing parameters under both water stress and no stress conditions. It was concluded that mungbean yield and yield components increased with combined application of 60 kg K ha −1 + 15 t OM ha −1 under full irrigated (no water stress) and limited irrigated (water stress) conditions.